EXTRACTION AND ABSORBANCE PROPERTIES TEST OF OIL FROM SACHA INCHI SEEDS (PLUKENETIA VOLUBILIS L.): EKSTRAKSI DAN UJI SIFAT ABSORBANSI MINYAK DARI BIJI TANAMAN SACHA INCHI (PLUKENETIA VOLUBILIS L.) - Selvi Puspita Dewi; Agus Setyo Budi; Jaja Jamaludin; Rahmat Setiawan Mohar; Nurfina Yudasari; Iwan Sugihartono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
The seeds of the sacha inchi plant (Plukenetia volubilis L.) have been extracted using the cold pressing method at a temperature of 45°C and a pressure of 600 bar or 60 MPa. Seeds come from sacha inchi plants grown at an altitude of 200 and 500 masl each with an oil volume of 100 ml. Testing of absorbance properties will be carried out using the UV-Vis spectrophotometer technique. So that the absorbance spectrum pattern are expected to provide information on the characteristics of the substance content possessed by the sacha inchi plant, namely lipids/fatty acids, proteins, tocopherols, phytosterols, phenolic components, fiber, antioxidants, carbohydrates, vitamins, polyphenols, and minerals.